2003
DOI: 10.5194/acp-3-1495-2003
|View full text |Cite
|
Sign up to set email alerts
|

Trace gas measurements from infrared satellite for chemistry and climate applications

Abstract: Abstract. Space-borne thermal infrared instruments working in the nadir geometry are providing spectroscopic measurements of species that impact on the chemical composition of the atmosphere and on the climate forcing: H 2 O, CO 2 , N 2 O, CH 4 , CFCs, O 3 , and CO. The atmospheric abundances obtained from the analysis of IMG/ADEOS measurements are discussed in order to demonstrate the potential scientific return to be expected from future missions using advanced infrared nadir sounders. Some strengths and lim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
63
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(63 citation statements)
references
References 47 publications
0
63
0
Order By: Relevance
“…Up till now, MOPITT has been unsuccessful in retrieving accurate CH 4 total columns from their data. Methane and carbon monoxide have been measured earlier by the Interferometric Monitoring of Greenhouse Gases (IMG) instrument on board the ADEOS satellite (Clerbaux et al, 2003;Barret et al, 2005). Recently, the EOS-AURA satellite was launched, carrying the Tropospheric Emission Spectrometer (TES) instrument, which is currently measuring CH 4 and CO (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Up till now, MOPITT has been unsuccessful in retrieving accurate CH 4 total columns from their data. Methane and carbon monoxide have been measured earlier by the Interferometric Monitoring of Greenhouse Gases (IMG) instrument on board the ADEOS satellite (Clerbaux et al, 2003;Barret et al, 2005). Recently, the EOS-AURA satellite was launched, carrying the Tropospheric Emission Spectrometer (TES) instrument, which is currently measuring CH 4 and CO (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This question is still subject to some controversy (Dueck et al, 2007) but has recently been confirmed in two studies Vigano et al, 2008). CH 4 profiles can also be retrieved from thermal infrared nadir sounders, as was shown from the IMG/ADEOS mission (Clerbaux et al, 2003) and more recently from the AIRS/AQUA and TES/Aura sounders (Xiong et al, 2008;Kulawik et al, 2008). Space-borne instruments working in a limb viewing geometry (ACE-FTS, HALOE, MIPAS) add information on the vertical distribution of methane but are only sensitive from the upper troposphere to higher altitudes (De Mazière et al, 2008;Raspollini et al, 2006;Park et al, 2004).…”
Section: Introductionmentioning
confidence: 92%
“…Agriculture is believed to be responsible for about 50% of global CH 4 emission induced by human activity [16]. Methane is produced when organic C decomposition in oxygen-deprived conditions, notably from crop grown under flooded conditions [17].…”
Section: Introductionmentioning
confidence: 99%